Ensiling Time and Mixed Microbe Fermented Liquid Modulate In Vitro Digestibility and Rumen Fermentation of Fermented Total Mixed Rations - Sineenart Polyorach; Wichai Suphalucksana; Ampon Klompanya; C. Yuangklang; Metha Wanapat; Seangla Cheas; Anusorn Cherdthong; Sungchhang Kang; Pongsatorn Gunun; Nirawan Gunun; Suban Foiklang; Phongthorn Kongmun; et al. (Veterinary Sciences, 2025)
< 0.05). Overall, moderate MMFL supplementation during a 14-day ensiling phase enhanced nutrient conservation and fermentation efficiency, suggesting practical value for improving FTMR utilization in ruminant systems. Further in vivo and economic evaluations remain necessary.
Keywords: Ruminant Nutrition and Digestive Physiology; Anaerobic Digestion and Biogas Production; Agriculture Sustainability and Environmental Impact